CLUSTER METHOD AND INTERACTION MECHANISMS IN THE ORGANIZATION OF GRAIN PRODUCTION - Dzholdasbaeva Gulnara; Beisekova Perizat (Academic Journal of Physical and Chemical Sciences, 2021)
The mechanism of distribution relations regarding the exchange of intermediate products, resources and services and the distribution of income from the sale of final products on the external market is an important part of economic relations within the cluster. The distribution mechanism ensures that the interests of cluster subjects are respected, and the mechanism of the grain product cluster is based on the fact that revenues from the sale of final products are distributed along the chain of the technological cycle, distributed through prices, tariffs, and centralized funds created by the cluster participants. In the grain-product complex, when using market prices, some enterprises become profitable, some-unprofitable, and when clustering, these processes can be preserved. An important element of the regional grain cluster is large grain companies and holdings that have concentrated large grain receiving enterprises for receiving, drying, storing and shipping grain. They include high-performance flour milling enterprises that have modern equipment from international manufacturers. These companies also include large, medium and small agricultural enterprises that produce grain, which have developed their own technological strategy and production structure, tactics, market behavior, and pricing policy. Regulatory mechanisms should be used to regulate relationships between cluster entities, ensure interests, coordinate individual and corporate goals, and regulate internal assortment, resource, price, and other proportions: standards of exchange and distribution relations; prices for products and final products sold. The issues of forming optimal economic relations between regional cluster entities, ensuring the implementation of individual and corporate goals, and regulating assortment, resource, and price interests are complex. The main part of economic relations within a cluster is the mechanism of distribution relations arising from the exchange of intermediate products, resources and services and the distribution of income from the sale of final products on the foreign market. The distribution mechanism should ensure that the interests of cluster members are realized. It should also be noted the peculiarity of regional clusters as a broad field of activity of enterprises.